Right to Information and Anti-SLAPP on Consumer Protection in Indonesia - Herawan Sauni; Putra Perdana Ahmad Saifulloh; Sonia Ivana Barus; Akhmad Akhmad; Asrul Ibrahim Nur (Sriwijaya Law Review, 2026)
Anti-Strategic Lawsuit Against Public Participation (SLAPP) is a provision that provides legal protection to the public who fight for public interests recognisedrecognised in legislation, usually in the environmental field; however, this study examines the projection of Anti-SLAPP for consumer protection. This research is normative legal research with a legislative, case, and conceptual approach, examining legal protection for consumers when submitting reviews on social media by highlighting the freedom of opinion guaranteed by legislation. The results of this study led to a balance of rights to information, and SLAPP was implemented for the benefit of all Indonesian people to foster meaningful participation in consumer protection. This study provides suggestions to Lawmakers on issuing regulations that specifically address Anti-SLAPP. These regulations are important to protect consumers from all threats, especially criminal entanglements, and as a guide for law enforcement officers in handling SLAPP cases in Indonesia. Lawmakers can issue regulations that, in revising the Consumer Protection Law, include anti-SLAPP provisions.